Edwardsiella ictaluri, an unusual cause of bacteraemia in a Nigerian child with acute bloody diarrhoea - Adepoju, Akinlolu A.; Adelaja, Adesola O.; Amoo, Abimbola; Orimadegun, Adebola E.; Akinyinka, Olusegun O. (International Journal of Research in Medical Sciences, 2021)
Enteric septicaemia of catfish was first detected in 1976 as an economically significant disease associated with commercial catfish production. Initially, Edwardsiella ictaluri was a host specific pathogen of catfish species but has also been reported from other hosts other than the catfish such as the zebrafish. E. ictaluri has not been isolated in humans hence it is not a zoonotic infection. There has been no previous report of isolation of this organism in humans. This was a case report of a 5 year old boy who presented with fever, vomiting, passage of bloody stool of 6 days and abdominal pain of a day duration. In the case of this 5 year old boy who presented with features of dysentery, blood culture using BACTEC™ grew E. ictaluri. E. ictaluri may be a pathogen which can infect humans just like another closely related species, Edwardsiella tarda. Although, E. ictaluri has not been reported in humans, could this be the first case? Non availability of diagnostic technique appropriate for its diagnosis may explain the rare incidence of the organism in humans, hence many cases would have been treated without isolating the organism.